Axil, a Member of the Axin Family, Interacts with Both Glycogen Synthase Kinase 3β and β-Catenin and Inhibits Axis Formation of Xenopus Embryos - Yamamoto, Hideki (American Society for Microbiology, 1998)
Using a yeast two-hybrid method, we identified a novel protein which interacts with glycogen synthase kinase 3β (GSK-3β). This protein had 44% amino acid identity with Axin, a negative regulator of the Wnt signaling pathway.We designated this protein Axil for Axin like. Like Axin, Axil ventralized Xenopus embryos and inhibited Xwnt8-induced Xenopus axis duplication. Axil was phosphorylated by GSK-3β. Axil bound not only to GSK-3β but also to β-catenin, and the GSK-3β-binding site of Axil was distinct from the β-catenin-binding site. Furthermore, Axil enhanced GSK-3β-dependent phosphorylation of β-catenin. These results indicate that Axil negatively regulates the Wnt signaling pathway by mediating GSK-3β-dependent phosphorylation of β-catenin, thereby inhibiting axis formation.